[Clinical and juridical aspects of management of neonates with invasive fungal infections] [Article in Italian] • Aspetti clinici e giuridici della gestione del neonato con infezioni fungine invasive - Vassilios Fanos; Angelica Dessì; Riccardo Fresa (Hygeia Press di Corridori Marinella, 2012)
Fungal infections are an important cause of morbidity and mortality in neonatology, especially in the case of neonates weighing ≤ 1500 grams (VLBW) at birth. In this review only those drugs indicated for paediatric use and commonly employed in neonatology are discussed in depth, which is to say fluconazole, amphotericin B, caspofungin and micafungin. Firstly, a review of the literature is presented by the neonatologist as concerns criteria for clinical use, with special emphasis on the efficacy/tolerability balance, underscoring the need not only for early diagnosis but also timely treatment and above all one that is "appropriate" to the seriousness of the pathology. Then the legal viewpoint concerning on-label and off-label antifungal therapies is presented. The choice of an antifungal drug for neonatal use cannot disregard certain preliminary considerations, in particular whether the drug has been properly tested for application in the neonatal field. Micafungin is the only on-label echinocandin adequately studied and authorized by the EMA for use in neonates. From a strictly juridical standpoint the on-label choice is a sign of diligent and prudent professional conduct; it is preferable since it is advantageous for patients' health and, in the case of litigation, provides the "best protection" for the physician. As concerns the use of off-label antifungals in neonatal intensive care, one of the requisites expressly prescribed by law is lacking, which is to say the "lack of a valid alternative" to their use.